2017
DOI: 10.12691/jfnr-5-7-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Pupils Attending Public Schools with and without School Feeding Programme in Hohoe Municipality, Ghana

Abstract: At-school lunch provision through the Ghana school-feeding programme (GSFP) is a child survival, health promotion and food security intervention implemented in selected schools in all 216 districts nationwide with the nutrition objective of reducing short-term hunger and malnutrition. The study assessed the impact of the Ghana School Feeding Programme (GSFP) on the nutritional status of participants. School-based cross-sectional survey using multi-stage sampling to select 417 pupils aged 3-12 years enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
8
2
Order By: Relevance
“…The third anthropometric indicators of undernutrition is wasting (thinness) which, in our study, had higher prevalence than the studies done in the western region of Nepal (12%) [44] and Burkina Faso (13.7%) [45]. In contrast, it is lower than a study from Ghana at 19.4% [46]. The possible explanation for these variations could be attributable to the difference in the parasitic infection, livelihood of the population Parasitic infection is one of the determinate factors for undernutrition as supporting by the studies conducted in different parts of the world [47,48].…”
Section: Discussioncontrasting
confidence: 76%
“…The third anthropometric indicators of undernutrition is wasting (thinness) which, in our study, had higher prevalence than the studies done in the western region of Nepal (12%) [44] and Burkina Faso (13.7%) [45]. In contrast, it is lower than a study from Ghana at 19.4% [46]. The possible explanation for these variations could be attributable to the difference in the parasitic infection, livelihood of the population Parasitic infection is one of the determinate factors for undernutrition as supporting by the studies conducted in different parts of the world [47,48].…”
Section: Discussioncontrasting
confidence: 76%
“…Comparing other areas in the baobab belt, the malnutrition prevalence in Kitui and Kilifi is higher than those reported among pupils in Hohoe municipality in Ghana, West Africa (Agbozo et al , 2017). There, the stunting rates lower than those reported in Kitui (46.8 per cent) and Kilifi (39.1 per cent) county as a whole.…”
Section: Discussionmentioning
confidence: 55%
“…Even between school fed and non-school fed children, no significant differences have been found in the prevalence of malnutrition (Abizari et al, 2014; Agbozo et al, 2017). Our findings are in line with those of Danquah et al (2012), who observed 15% stunting, 12% underweight, 4% thinness and 4% obesity among school children who benefitted from the GSFP in the Ashanti region of Ghana.…”
Section: Discussionmentioning
confidence: 92%
“…Close to half (41.9%) were given money to buy food/ snack in school or sent food from home. Detailed background characteristics of the study participants have been described elsewhere (Agbozo et al, 2016(Agbozo et al, , 2017.…”
Section: Demographic Characteristics Of Participantsmentioning
confidence: 99%